2017
DOI: 10.1016/j.amsu.2017.09.015
|View full text |Cite
|
Sign up to set email alerts
|

The Birmingham experience of high-pressure methylene blue dye test during primary and revisional bariatric surgery: A retrospective cohort study

Abstract: IntroductionLeak following bariatric surgery continues to be associated with morbidity and rarely mortality. With improvement in surgical techniques and stapler design, leak rates have reduced drastically. Intra-operative high pressure Methylene blue leak test (HPMB) is one of the techniques employed to confirm integrity of anastomoses and staple lines. Despite this, evidence for its use remains limited. We evaluated the role of HPMB in detecting and preventing leaks.MethodsA retrospective cohort of consecutiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Other studies have claimed that there is no advantage in performing the MBT during SG. Kirby et al 18 failed in trying to establish a clinical value for the MBT in bariatric procedures. With a sample of 225 patients who underwent SG, they found three cases of postoperative leaks, all of which had negative MBT.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Other studies have claimed that there is no advantage in performing the MBT during SG. Kirby et al 18 failed in trying to establish a clinical value for the MBT in bariatric procedures. With a sample of 225 patients who underwent SG, they found three cases of postoperative leaks, all of which had negative MBT.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, authors have also claimed that another reason not to perform the MBT is the risk of anaphylaxis 18 . Although a few cases of allergic reactions have been reported with the use of the methylene blue, there is no report of anaphylactic shock following the use of this dye 2,10 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(23) We don't routinely perform intra-operative leak tests (IOLT) in LSG, as they are unreliable and may be more harmful than benificial. (37)(38)(39)(40) Bingham et al (38) performed a retrospective multicenter study to assess the benefits and efficacy of routine IOLT in LSG, the reported that IOLT had -very poor sensitivity‖, as 91% of patients with post-LSG leaks had negative IOLT, and that routine IOLT did not decrease theincidence of post-LSG leaks. Bingham et al (40) in another retrospective study, found that all patients with post-LSG leaks had negative IOLT.…”
mentioning
confidence: 99%